GLOBALIZATION AND LOCAL CULTURE: ADAPTATION AND ADOPTION FOR SUSTAINABLE DEVELOPMENT IN NIGERIA - Efe Ekuerhare, Sylvia (African Journal of Social and Behavioural Sciences, 2024)
In the midst of globalization, the indigenous culture could undergo a transformation that could either hamper or enhance the development process of the local culture due to several issues, such as the inability of the imported tradition or development effort to fit into the local environment. Therefore, this paper examined how adapting or adopting globalisation could transform the local culture towards attaining sustainable development in Nigeria. It adopts a systematic review method, using search engines such as google scholar, Google, ResearchGate, among others, considering articles between 2010 and 2023, and content analysis was used to group materials into major themes, thereby subjecting them to thematic analysis towards addressing the objective of the study. The findings of the study revealed that when globalisation and its elements transcend into local culture they do not synchronise with or fit into the local culture, such efforts could deter and distort local culture and its development in the long run. However, when they are tailored to fit into the local culture, such efforts could enhance development and, hence, sustainable development. In conclusion, globalisation and its elements tailored to the mainstream local culture could either be adopted or adapted into the local environment, depending on the peculiarity of the local culture, to be able to enhance sustainable development in such local culture.